Principles of Surgical Treatment of Soft Tissue Sarcomas - Gonzalez, Marcos R. (2025)
Soft tissue sarcoma (STS) is a group of highly heterogeneous tumors of mesenchymal origin that have variable primary site locations and clinical behavior. Despite the broad diversity of STS, the standard of care involves surgical resection with or without radiation therapy (RT) to control local recurrence and systemic treatment in select cases. The complexities of STS require a critical understanding of the preoperative work-up process, surgical treatment, and postoperative management. Advanced imaging plays a vital role in the characterization of the soft tissue mass, preoperative biopsy planning, and disease staging. Surgical treatment prioritizes wide resection with negative margins, supported by newer margin classification systems for better prognosis. Further, advancements in surgical technique have enabled limb-salvage surgery to largely replace amputation in the management of these tumors. Additional surgical considerations, such as nerve preservation, vascular reconstruction, and complex tissue closure, further highlight the complexity of STS management. Lastly, postoperative follow-up is critical for the early detection of local or distant recurrences. For complex cases, such as unplanned excisions or invasive tumors, strategies like re-resection may be beneficial. Ongoing research into imaging, chemotherapy, and targeted therapies will further refine management strategies, especially in complex and recurrent cases. This review highlights the essential aspects of STS surgical management and underscores the need for coordinated, multidisciplinary care to enhance both survival and quality of life for affected patients.